Pengaruh Kesiapan Ekosistem Inovasi terhadap Kemampuan Pemasaran Digital melalui Transformasi Digital dan Adopsi Pemasaran Digital sebagai Variabel Mediasi pada UMKM di Kota Padang - Adito Aulia Andrian; Yunita Engriani (Universitas Negeri Padang, 2025)
The purpose of this study is to determine the role of digital marketing competency in facilitating innovation ecosystem readiness among MSMEs in Padang City, and how digital transformation and the adoption of digital marketing strategies mediate this relationship. The methodology chosen by the authors is aptly described as a descriptive causal study. Micro, small, and medium enterprises (MSMEs) in Padang City that utilize digital marketing strategies constitute the population of this study. In 2024, the researchers conducted this study. The sample for this study consisted of 324 people. We used Google Forms to disseminate an online poll that collected data. Data analysis was conducted using SmartPLS. Among the many conclusions drawn from the research data are the following: (1) innovation ecosystem readiness has a positive and significant impact on digital transformation; (2) innovation ecosystem readiness has a positive and significant effect on digital marketing adoption; (3) innovation ecosystem readiness has a positive and significant effect on digital marketing capability; (4) digital transformation has a positive and significant effect on digital marketing adoption; (5) digital transformation has a positive and significant effect on digital marketing capability; (6) digital marketing adoption has a positive and significant effect on digital marketing capability; and (7) innovation ecosystem readiness positively and significant influences digital marketing capability through digital transformation and digital marketing adoption as mediating variables. MSMEs in Padang City must improve their search engine optimization skills to maintain competitiveness and consistently rank high on search engines.